Logistics Mode Selection Model Based on Fuzzy multi-objective Programming (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Logistics mode selection is one of the most important activities of supply chain management. An important way to make competitor advantage is select an optimal Logistics mode for the enterprise. Logistics mode selection is a multi-criterion decision making problem in which criteria have different relative importance. In practice, many input information are known precisely. The fuzzy set theories can be used due to the imprecision of information. In this paper, a fuzzy multi-objective decision-making model which is equivalent to solving crisp model by using max-min approach is developed to handle effectively the vagueness of input data in the process of Logistics mode selection. Also, an additive model taking into account the objectives’ weights is presented further in the end of this paper.